Rhizaxinella Keller 1880 ... - Plotkin, Alexander S.; Janussen, Dorte (Zenodo, 2008)
Genus Rhizaxinella Keller, 1880 Diagnosis (sensu van Soest 2002): Pedunculate sponges, with spherical, ovoid or cylindrical body carried on a simple or ramified stalk, normally attached to the substrate by a root system; usually an apical oscule. Body with a moreorless radial skeleton and with brushes of spicules at the surface, skeleton of the stalk a tightly packed mass of aligned megascleres, bound by spongin. Megascleres are tylostyles of different sizes with raphides in trichodragmas. Type species: Rhizaxinella clavigera Keller, 1880 (by monotypy) = junior synonym of Alcyonium pyrifera delle Chiaje, 1828. ... : Published as part of Plotkin, Alexander S. & Janussen, Dorte, 2008, Polymastiidae and Suberitidae (Porifera: Demospongiae: Hadromerida) of the deep Weddell Sea, Antarctic *, pp. 95-135 in Zootaxa 1866 on page 126, DOI: 10.5281/zenodo.183878 ...